Allostratigraphy of Punung Paleoreef based on Lithofacies Distributions, Jlubang Area, Pacitan Region-East Java - Premonowati Premonowati; B. Prastistho; I. M. Firdaus (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i2.140Lithologically, Punung Formation as a paleoreef comprises coral boundstone rhodolith, algal grainstone, algal packstone, algal wackestone, algal floatstone, and algal rudstone. It is dominated by red algae and had formed a fringing reef in a warmly shallow marine environment. They built seven phases of paleoreef complex. Each paleoreef complex has been bounded by a local unconformity that is characterized by caliche. The Jaten Formation has becomes the base of the Punung paleoreef which build up by an angular unconformity contact on uppermost part. It consists of tuffaceous wacky sandstone with silicate cement. The formation as the reef base indicates two factors. The external factor because of the decrease of a volcanic activity and the internal one was caused by the depositional environment of the Jaten Formation becoming shallower. The subsurface runoff systems in many caves (like: Jaran cave and others) have the same southward direction to the dipping direction of algal grainstone lithofacies of Punung Formation. The vertical caves are formed by a jointing system.